Enhancing Problem-Solving Skills in Secondary Mathematics Education Through Collaborative Learning - Junaid, Albasri (Journal of Interdisciplinary Perspectives, 2025)
This study investigated how collaborative learning strategies enhance problem-solving skills among junior high students at Maimbung Technical Vocational High School. Using a descriptive-correlational design, 100 purposively selected students participated. Strategies examined included Think-Pair-Share, Jigsaw, Collaborative Problem-Solving, and Team-Based Learning, alongside demographic factors such as age, gender, grade level, learning style, and parental education. Most students were female, aged 13–14, preferred the Reading/Writing style, and had college-educated parents. Overall, collaborative strategies were viewed as effective in promoting problem-solving, teamwork, engagement, and critical thinking. No significant differences emerged across demographic groups, but strong positive correlations were found among Jigsaw, Collaborative Problem-Solving, and Team-Based Learning, underscoring their complementary roles. However, the study's scope—limited to one school and its descriptive design—restricts causal conclusions and broader applicability. It also did not explore long-term effects, qualitative aspects, or online learning contexts. The study recommends training and resources for teachers, parental support for home learning, and student participation in group activities. Future research should use experimental and longitudinal methods, explore group dynamics, and examine collaborative learning in varied educational settings to address current gaps and better understand its sustained impact on academic performance.